Couple's concordance and discordance in household decision-making and married women's use of modern contraceptives in Bangladesh - Jalal Uddin; Muhammad Zakir Hossin; Mohammad Habibullah Pulok (BMC, 2017)
Abstract Background Although a large body of studies documents that women's autonomy in the household is associated with better reproductive health outcomes, these studies typically examined autonomy only from women's point of view. The current study employs husband's and wife's perspectives together to examine the relationship between the decision-making arrangements in the household and the women's use of modern contraceptives in Bangladesh. Methods The study used the couple dataset of 2007 Bangladesh Demographic and Health Survey. The sample was comprised of 3336 married couples. Binary logistic regression models were used to examine the associations between the selected items on household decision-making and the use of modern contraceptives. Results Our results indicate that the couples disagree considerably as to who in the household exercises the decision-making power. The pattern of decision-making regarding visiting family and relatives emerged as an important predictor of use of modern contraceptives in the multivariate regression analysis. The results suggest that compared to the couple's concordant joint decision-making, the husband-only decision-making is associated with lower odds of contraceptives use (OR 0.49; 95% CI 0.28-0.85). Only a small part of this association is explained by spousal communication about family planning issues while the socio-demographic correlates hardly affected the association. On the contrary, the wife-only decision-making did not result in increased contraceptives use (OR 0.71; 95% CI 0.45-1.13). Conclusions The study findings imply that women's greater autonomy may not necessarily result in improved reproductive health behavior, and therefore, a balance of power in the spousal relationship is warranted.